Pengukuran Motivasi Berwirausaha Mahasiswa melalui Pembelajaran Bisnis Berbasis Proyek - Nugrahani, Cahaya; Marjukah, Anis; Sri Nugroho, Arif Julianto; Haryono, Purwo (Surakarta Management Journal, 2023)
This research has an urgency to form a project-based entrepreneurial learning model as a superior learning model to create competitive undergraduate graduates. The purpose of activity is to test whether the learning model obtained by students through project-based entrepreneurship education can strengthen attitude variable towards students' interest in entrepreneurship. The research method is in the form of experimental research on model development (R&D) through experimental and control variables. Sampling was used purposively on 60 students. Operationalization of the project-based business learning model includes input integration involving students who have initial pilot business projects, processes with classical training activities on business feasibility, innovation, business motivation, role playing, business visits to assist prospective new entrepreneurs accompanied by monitoring activities. The results of the activity provide a conclusion that project-based business learning activities are effectively carried out which is proven by the emergence of students’ interest in the real practice of opening